(untitled) (Research, Society and Development, 2021)
When entering university, students go through several transformations in their academic, familiar and social contexts that may make them prone to develop psychopathologies such as anxiety and depression. In this context, this research aimed to identify indexes of depression and anxiety in students in their early and late phases of the Psychology major in a University Center in the countryside of Ceará. The research was conducted with 176 subjects. Tools for data collection were a socioeconomical survey, Beck Depression Inventory, and Beck Anxiety Inventory. In the results, it was observed that 55,42 % of the individuals presented symptoms of moderate and severe anxiety, and 31,24% of the individuals presented symptoms of moderate and severe depression, both prevailing more in women. The practice of physical exercises and involvement in collective activities were associated to prevent these diseases and to improve well-being. The conclusion points to the necessity of deepening the understanding of this phenomenon in such population given that they are individuals in evolving processes and, therefore, more vulnerable.